Dementia : presentations, differential diagnosis, and nosology - Emery, V. Olga B.; Oxman, Thomas E. (Johns Hopkins series in psychiatry and neuroscience., 2003)
Annotation In this new edition of the acclaimed Dementia: Presentations, Differential Diagnosis, and Nosology, V. Olga B. Emery, Ph. D., and Thomas E. Oxman, M.D., bring together a distinguished group of medical authorities - including many who have done seminal research in this field - to discuss the spectrum of dementing disorders and explain their overlap, presentations, and differential diagnosis. The chapters present original data as well as material from the authors' clinical experiences. Current classification systems are evaluated and modified to better account for common presentations of dementia. Thoroughly revised, updated, and expanded, the second edition includes new material on neuroimaging, genetics, the role of inflammation in Alzheimer disease, retrophylogenesis in Alzheimer memory, and on AIDS dementia. In addition, each chapter includes a new section entitled describing clinical applications.